Identity types and learners' attitudes in language learning: Voices from students of medical sciences - Hamid Mahmoodi; Mehry Haddad Narafshan (Tabriz University of Medical Sciences, 2020)
Background: The academic level of each society is assessed through the level of its students' education. Students need to update their knowledge based on the latest achievements obtained throughout the world. What can serve this purpose is "language" as a key instrument. Methods: The current mixed methods study reviewed attitudes of Iranian medical sciences students towards learning English Language with a focus on their identity type. To this end, 372 students of medical sciences (medical, paramedical, and nursery and midwifery) completed two questionnaires and participated in a semi-structured interview investigating participants' attitudes toward language learning. Results: The results indicate that the students had a considerable appreciation for the English language, particularly in enhancing job opportunities for them in the future and helping them to keep up with technological developments in the world. Moreover, the English language was considered a way of feeling more confident and enriching their intercultural horizons in establishing interpersonal skills. There were also tendencies towards the English language as a prestigious language with a high social level and a channel to have good relationships with other people in their field. To some extent, they knew English as the transmission of professional knowledge providing academic support; foursome of them, it was considered just a university course to pass. It was also realized that the differences in their perceptions were not affected by their identity type, suggesting a unique path of identity type and certain attitudes for students of medical sciences. Conclusion: In brief, with the English language considered as a growing global status and the increasing interpretation of the impact that these shifts have on attitudes towards learning the English language, there is a need for theoretical and practical exploration of learners 'attitudes towards the English language.